2021
DOI: 10.3390/ijms22179283
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin-Induced Autophagolysosome Formation Is Partly Prevented by Mitochondrial ROS Elimination in DOX-Resistant Breast Cancer Cells

Abstract: Since its discovery, mitophagy has been viewed as a protective mechanism used by cancer cells to prevent the induction of mitochondrial apoptosis. Most cancer treatments directly or indirectly cause mitochondrial dysfunction in order to trigger signals for cell death. Elimination of these dysfunctional mitochondria by mitophagy could thus prevent the initiation of the apoptotic cascade. In breast cancer patients, resistance to doxorubicin (DOX), one of the most widely used cancer drugs, is an important cause o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
(33 reference statements)
1
12
0
Order By: Relevance
“…The results of this study revealed high glucose consumption in the MCF-7 cells with drug resistance. Similarly, Ahmadpour et al demonstrated that lactate production and glucose consumption were higher in MCF-7 cells with doxorubicin resistance than in parental MCF-7 cells, suggesting that MCF-7 drug-resistant cells exhibit a predominance of glycolytic metabolism [37]. Our data revealed that in the MCF-7-D500 cells, G6P and FBP levels were signi cantly increased, whereas those of 2PE and DHAP were signi cantly decreased.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The results of this study revealed high glucose consumption in the MCF-7 cells with drug resistance. Similarly, Ahmadpour et al demonstrated that lactate production and glucose consumption were higher in MCF-7 cells with doxorubicin resistance than in parental MCF-7 cells, suggesting that MCF-7 drug-resistant cells exhibit a predominance of glycolytic metabolism [37]. Our data revealed that in the MCF-7-D500 cells, G6P and FBP levels were signi cantly increased, whereas those of 2PE and DHAP were signi cantly decreased.…”
Section: Discussionsupporting
confidence: 76%
“…Reactive oxygen species (ROS) production in mitochondria was higher in MCF-7 cells with doxorubicin resistance than in parental MCF-7 cells [37]. Excessive ROS production may lead to a glycolysis reaction switch to the HBP through the inhibition of the glycolytic enzyme GAPDH [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, targeting glycolysis by targeting glucose transporters or enzymes of the glycolytic pathway can reverse chemoresistance [ 33 ]. Mitochondrial impairment was recently described in MCF-7dox cells with a predominant glycolytic metabolism, with a strong impairment of Cx I structure and function [ 34 ]. Our study further demonstrates that silencing SAMMSON in this model not only enables us to slow glycolysis down, but it also triggers a stimulation of the oxidative metabolism by increasing mitochondrial translation pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Research has recently provided evidence of a high ROS production in MCF-7dox cells [ 34 ]. In the present study, we showed that the silencing of SAMMSON decreased this ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…According to the concept of patient-focused design, vascular embolism is a local treatment that has fewer side effects than chemotherapy. The second and third steps adopted both a nanoparticle strategy and codelivery strategy, combining graphene nanoparticles with the chemotherapy drug doxorubicin (Dox) [6]. Nanoparticles were used as the drug carrier, as they can prolong the retention time of the drug in the blood as well as reduce opsonin absorption and reticuloendothelial system (RES) recognition [7].…”
Section: Introductionmentioning
confidence: 99%